Appearance-based trust behaviour is reduced in children with autism spectrum disorder. (November 2015) - Ewing, Louise; Caulfield, Frances; Read, Ainsley; Rhodes, Gillian
Typical individuals make rapid and reliable evaluations of trustworthiness from facial appearances, which can powerfully influence behaviour. However, the same may not be true for children with autism spectrum disorder. Using an economic trust game, the current study revealed that like typical children, children with autism spectrum disorder rationally modulate their trust behaviour based on non-face cues to partner trustworthiness (e.g. reputation information). Critically, however, they are no more likely to place their trust in partners with faces that look trustworthy to them, than those that look untrustworthy. These results cannot be accounted for by any group differences in children's conceptualization of trustworthiness, ability to read trustworthiness from faces or understanding of the experimental paradigm. Instead, they seem to suggest that there may be a selective failure to spontaneously use facial cues to trustworthiness to guide behaviour in an ecologically valid context.